PENGARUH LAMA EKSTRAKSI MENGGUNAKAN ULTRASONIK TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN TEMPUYUNG (Sonchus arvensis L.) - Miradita Lestari, Ni Made; Yusa, Ni Made; Ayu Nocianitri, Komang (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2020)
This study was conducted to determine the effect of time extraction using ultrasonic method on the antioxidant activity of tempuyung leaves ethanol extract and to find out the exact time to get tempuyung leaves ethanol extract with the highest antioxidant activity. The experimental design used in this study was a completely randomized design with time extraction as a treatment. The treatment consisting of five levels, which is 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes using ultrasonic method with temperature 45oC and frequency 37 kHz. All treatments were repeated three times so that they were obtained 15 experimental units. The data obtained were analyzed of variance and if the treatment had significant effect followed by Duncan’s Multiple Ring Test. The results showed that the time extraction treatment had a very significant effect (P<0.01) on yield, total phenol, total flavonoids, total tannin, and antioxidant activity from tempuyung leaves ethanol extract. The best treatment was 30 minutes which produced highest antioxidant activity of 58,60 % with IC50 262,82 mg/L included in the weak category, yield 18,60%, total phenolic 55,05 mg GAE/g, total flavonoid 38,14 mg QE/g, total tannin 8,82 mg TAE/g.